(untitled) (Journal of the College of Basic Education, 2022)
This study is a try to read the manner of writing for the female Arab pre-Islamic poets and their poetic language, where our method was the study of the pioneer phenomena in their lingual use and how they invest the different and various styles and mixing them to mark their styles and poetic language and with a special pattern showing their ability and unique creativeness. The research is an analytical study for the styles for the language of the poets basing on the applying some of lingual and stylish standard to distinguish the poetic performance in its speech, grammatical, phonolitical preference levels to explore their ability to mold their stylish and imaginative abilities to transfer the lingual reality to poetic reality raising their poetic texts to the ultimate level of the poetic art